A Comparsion between the impacts of two methods of training in characteristic signs, symptoms and risky factors of increased intracranial pressure in head injuryes Patients upon the cognitive domain of a number of nurses serving at some selected hospitals of tehran Medical sciences university in 1375 - F rasouli; P Haj Amiri; M Mahmoodi; N Rasool Zadeh (حیات, 2000)
This is a quasi - experimental study, made with the objective of a comparsion between the impacts of two methods of training in characteristic signs ,symptoms and risky factors of increased intracranial pressure in head injury patients upon the cognitive domain of a number of nurses serving at some selected hospitals of Tehran Medical Sciences University in 1375 . The samples were made of 74 male and female nurses from CCUs and / orsurgery wards , who were divided randomly into two groups of 35 and 39 nurses respectively . The training approach concerning the former group was made through lectures, while that of the latter used computers .The data collection tool was a questionnarie consisting of two parts . The first part dealt with individual demographies and the second part included 40 questions . 25 of which were multiple choice and the remaining 15 were matching questions about the characteristic signs, symptoms and risky factors of increased intracranial pressure . The questionnaries werefdled in by the samples in two pre - test and post - test stages , while the researcher was present. The collected data were organized into 24 tables and are analized throughdescriptive and inferential statistic methods . Absolute , relative and mean indicatots , mean standard deflation , mean variation, standard deriation of mean variation , as well as McNemar, paired and student tests were used for the analysis. The findings demonstrate that the number of those filling in the questionnaries increased following the application of lecture and computerized training methods..The statistic results of the paired test in relation with the lecture method ( t~12.312 , of - 34 ) show a meaningful difference in comparison with the computerized method ( t=q.528 , of- 35) atp< 0.01 level. The results of thestudent test, however, did not reveal a significant statistic difference when the impacts of the two approaches are compared. The study results, also make it clear that in lecture approach , the mean variation of the grades given to the cognitive domain shows a significant increase in terms of all the variables excluding those of : not obtaining information during education , in - service training courses , and other cases and records of serving at CCUs or neurology surgery wards for more than 48 months. At the conclusion , the applications of the results of this study are mentioned, and suggestions are made - on the basis of the findings here - to bring the findings and results of the study to Completion and also to make further studies.